CP-133 Name patient program with siltuximab in multicentric castleman's disease: a case report. (24th March 2015) - Bocchio, F; Bonfichi, M; Calvi, M; Tizzoni, M; Rebagliati, G
Abstract : Background: Multicentre Castleman's disease (MCD) is a rare lymphoproliferative disorder driven by dysregulated interleukin-6 (IL-6) production. MCD can be associated with human immunodeficiency virus (HIV) and Herpes Virus 8 (HHV8) infections. Siltuximab is a chimeric monoclonal antibody with high binding affinity for IL-6, blocking the abnormal growth of immune cells. Siltuximab was designated an orphan drug on November 2007. FDA (April 2014) and EMA (May 2014) approved siltuximab in subjects with HIV-negative, HHV8-negative MCD. In Italy siltuximab can currently only be requested as part of a named patient program (NPP), supplied free of charge by the manufacturing company. Purpose: To describe a case report and analyse current treatment options for MCD and the safety profile of siltuximab. Material and methods: We examined siltuximab treatment prepared by the Pharmacy from February to September 2014. Results: One 65-year-old man, 107 kg, was diagnosed with MCD in our centre and treated with siltuximab 11 mg/kg IV every 3 weeks for 10 cycles with a good response. A computed tomography (CT) check showed reduction of mediastinal nodal enlargement without new disease locations. Siltuximab was well tolerated and demonstrated a consistent safety profile. Conclusion: Current results strongly suggest that siltuximab, the first drug approved for MCD, is effective and safe. Further studies are needed in order to confirm the validity of these results. References and/or Acknowledgements: van Rhee F, Fayad L, Voorhees P, et al . Siltuximab, a novel anti-interleukin-6 monoclonal antibody, for Castleman's disease. J Clin Oncol 2010;28(23):3701–8 Kurzrock R, Voorhees PM, Casper C, et al . A phase I, open label study of siltuximab, an anti-IL-6 monoclonal antibody, in patients with B-cell non-Hodgkin lymphoma, multiple myeloma, or Castleman disease. Clin Cancer Res 2013;19(13):3659–70 No conflict of interest.